Human-animal chimeras for vaccine development: an endangered species or opportunity for the developing world? - Daar Abdallah S; Singer Peter A; Bhan Anant (BMC, 2010)
Abstract Background In recent years, the field of vaccines for diseases such as Human Immunodeficiency Virus (HIV) which take a heavy toll in developing countries has faced major failures. This has led to a call for more basic science research, and development as well as evaluation of new vaccine candidates. Human-animal chimeras, developed with a 'humanized' immune system could be useful to study infectious diseases, including many neglected diseases. These would also serve as an important tool for the efficient testing of new vaccine candidates to streamline promising candidates for further trials in humans. However, developing human-animal chimeras has proved to be controversial. Discussion Development of human-animal chimeras for vaccine development has been slowed down because of opposition by some philosophers, ethicists and policy makers in the west-they question the moral status of such animals, and also express discomfort about transgression of species barriers. Such opposition often uses a contemporary western world view as a reference point. Human-animal chimeras are often being created for diseases which cause significantly higher morbidity and mortality in the developing world as compared to the developed world. We argue in our commentary that given this high disease burden, we should look at socio-cultural perspectives on human-animal chimera like beings in the developing world. On examination, it's clear that such beings have been part of mythology and cultural descriptions in many countries in the developing world. Summary To ensure that important research on diseases afflicting millions like malaria, HIV, Hepatitis-C and dengue continues to progress, we recommend supporting human-animal chimera research for vaccine development in developing countries (especially China and India which have growing technical expertise in the area). The negative perceptions in some parts of the west about human-animal chimeras can be used as an opportunity for nurturing important vaccine development research in the developing world.